Are common candidacies viable in the state of Guanajuato? A comparative study of the 2024 local elections in Mexico - Pantoja López , Edgar Everardo (Southern perspective / Perspectiva austral, 2024)
Introduction: The study addressed the goals that political parties pursued within democratic systems. It was considered that parties were not static structures, but that their goals varied according to political and social conditions. Based on Strøm's (1990) classification, three main orientations were established: vote seeking, office winning and policy making.Development: Vote-oriented political parties prioritized their electoral performance, often without necessarily seeking public office. In Mexico, this phenomenon was observed due to the relationship between public funding and votes obtained. On the other hand, parties focused on obtaining office sought benefits associated with political power, while those focused on policy implementation prioritized the implementation of their ideology and governmental agenda. In addition, the influence of the institutional context on parties was analyzed, noting that electoral regulations and the structure of the political system conditioned their strategies and objectives.Conclusion: It was concluded that political parties did not follow unique objectives, but that their strategies varied according to their context and needs. Electoral competition, the legal framework and the internal structure of each party determined their orientation. In the case of Mexico, democratization and electoral reforms influenced party dynamics, promoting pragmatism and the formation of strategic alliances.